In vivo distribution of human milk leucocytes after ingestion by newborn baboons. Issue 7 (July 1989) - Jain, L; Vidyasagar, D; Xanthou, M; Ghai, V; Shimada, S; Blend, M
Abstract : The in vivo distribution of enterally administered human milk leucocytes labelled with indium hydroxyquinoline (111In) was studied in premature baboons. The animals were killed at 72 hours of age and tissue samples examined for radioactivity. Maximum activity was found in the luminal contents, and activity in the liver and spleen was higher than in bone marrow, the site where free isotope is normally deposited. These findings suggest that some intact milk leucocytes may cross from the gastrointestinal tract into the neonatal circulation. Also the high activity in gastrointestinal tissue that had been washed several times indicates that leucocytes adhere to mucosa or lie intramurally. We speculate that the presence of leucocytes in the gastrointestinal tract 60 hours after a single breast feed can provide an important defence mechanism against infection.